Regard critique sur une période sans but - Farinelli, Patrizia (Ars et humanitas, 2015)
The density of motifs in the myth of Antigone could itself explain the reason for such a large number of interpretations and modernized versions of the myth. In these the conflict between the inner voice of the individual and the law of the state is placed at the very centre, thus primarily indicating a political interpretation; however, the ways in which the conflict are shown also allow for other interpretations: anthropological, ethical, psychological ones. Without circumventing the possibility of timeless meanings, Valeria Parella's re-working of the Sophocles tragedy (Antigone, 2012) represents a direct confrontation with the present. The updated elements are to be found not only in the replacing of a forbidden burial with the motif of illegal euthanasia; rather, they manifest themselves especially in the rather critical view of contemporary history. The author's attention is directed at an aimless period and the public's inactive awareness. Her Antigone - which is formed also by means of the semiotics of sight and movement - is a call to seek out a sense of responsibility and a call to action, to seeking a way out of a period of stagnation, and it possesses a clearly-expressed ethical and social political importance. Dubious is the very powerfully expressed concept of truth which permeates the discourse, and even the overly explicit means with which this call is realised: the heroes have a tendency to simplification, and the function of words is limited merely to a means of communication, even though one would expect something else from a literary text, that it might prompt special reflection on complexity.
Keywords: Antigona; epistemologija; epistemology; italijanska književnost; miti; mythology; myths; odgovornost; Parrella; Parrella, Valeria; responsibility; semiotics; semiotics of sight; semiotika